Safety of mass sports events - Robert Socha; Bernadrd Wiśniewski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
Full assurance of safety during mass events is a complex process, subject to provisions of generally applicable law. These provisions regulate in detail all basic obligations and requirements provided for this particular kind of events. However, in the course of time some of the regulations provided for in the Polish legal system gave rise to doubts about their specificity. In this paper the authors discuss and clarify the areas which are necessary to ensure the highest level of safety of sports events i.e. the circulation of information during the preparation, organization and execution phase of the event, organization of evacuation as well as cooperation of organizers with entities designated for protection. The study is of utilitarian character and it encourages extensive discussion related to the field of provision of safety during sports events.